PERKAWINAN BEDA AGAMA DALAM ADAT TORAJA: STUDI KASUS PUTUSAN PN MAKALE NO. 2/PDT.P/2022: Interfaith Marriage In Toraja Customary Society: Case Study Of Pn Makale Decision No. 2/Pdt.P/2022 - William Zerach El; Endang Pandamdari (Reformasi Hukum Trisakti, 2025)
Marriage is a physical and spiritual bond between a man and a woman as husband and wife, aiming to form a happy and lasting family based on the belief in God Almighty. A marriage is considered valid if conducted according to the laws of the respective religions and beliefs of the parties involved. Marriage is governed by the Marriage Law and the Compilation of Islamic Law. In Toraja customary law, interfaith marriage is not regarded as an issue or a requirement for the validity of a customary marriage. However, it raises the question of whether the Makale District Court Decision No. 2/Pdt.P/2022/PN Mak, which approved an interfaith marriage, aligns with the applicable marriage laws in Indonesia. To address this issue, normative juridical research was conducted, supported by primary data. The collected data was qualitatively analyzed, combining secondary data with primary data, and conclusions were drawn using the deductive method. The research findings, based on secondary data and interviews, reveal that Toraja customary law does not view interfaith marriage as a problem or a condition for the validity of a customary marriage.